Performance and Value Of RGEC Sharia Bank: Evidence From Indonesia - Kurnia, Rahmat; Maminiaina Heritiana Sedera, Rakotoarisoa; Hasan, Nugraha (Universitas Islam Negeri Alauddin Makassar, 2024)
in progras